Management Statement and Financial Memorandum between Department for Infrastructure and Northern Ireland Water Limited (NIW) : Effective from 1 April 2012, Revised 31 January 2017.: Effective from 1 April 2012, Revised 31 January 2017. ([2017]) - Northern Ireland Water,; Northern Ireland., Department for Infrastructure,
No abstract available